1979
DOI: 10.1073/pnas.76.6.2932
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of a mouse immunoglobulin mu chain.

Abstract: The complete amino acid sequence of the mouse ,g chain from the BALB/c myeloma tumor MOPC 104E is reported. The CA region contains four consecutive homology regions of approximately 110 residues and a COOH-terminal region of 19 residues. A comparison of this p chain from mouse with a complete ;& sequence from human (Ou) and a partial A chain sequence from dog (Moo) reveals a striking gradient of increasing homology from the NH2-terminal to the COOH-terminal portion of these It chains, with the former being the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 41 publications
5
61
1
Order By: Relevance
“…These include the carboxyl-terminal constant domains and the adjoining 19-residue tails that are unique to secreted tL and a chains and contain the penultimate cysteine residue through which polymerization is effected (1, 2). Kehry et al (30) have found that the carboxyl-terminal regions of ,u chains are considerably more conserved than the amino-terminal regions, and similar results have recently been obtained for a chains (31). The mouse and human data from these studies are presented in Table 1 The question then arises as to why the polymerization process has been maintained over the evolution of the immunoglobulins.…”
supporting
confidence: 63%
“…These include the carboxyl-terminal constant domains and the adjoining 19-residue tails that are unique to secreted tL and a chains and contain the penultimate cysteine residue through which polymerization is effected (1, 2). Kehry et al (30) have found that the carboxyl-terminal regions of ,u chains are considerably more conserved than the amino-terminal regions, and similar results have recently been obtained for a chains (31). The mouse and human data from these studies are presented in Table 1 The question then arises as to why the polymerization process has been maintained over the evolution of the immunoglobulins.…”
supporting
confidence: 63%
“…There is precedent for such a possibility. Kehry et al [33,341 found that in the p chains of both human and mouse IgM, two out of five N-linked glycans remained in a high-mannose form in the mature protein. In the case of IgM, the position of these unprocessed high-mannose glycans was conserved between species [33, 341. The nonspecifically precipitated 80-kDa protein seen in Figs 5 and 6 was converted to a 70-kDa form at all time points after treatment with endoglycosidase H (Fig.…”
Section: Endoglycosidase H Sensitivity Of Human Pc-1mentioning
confidence: 99%
“…The four amino acid sequences show that Cys and Trp residues were the most frequently conserved out of all amino acids in mouse and rat Ig classes, respectively. Cys and Trp are suggested to play important roles in maintaining Ig structure [6]. In particular, Cys is essential for the formation of intrachain disulfide bonds or bridges and for the polymerization of IgM and IgA [14].…”
Section: Discussionmentioning
confidence: 99%